Innovation and Accountability in Teacher Education Setting Directions for New Cultures in Teacher Education (Teacher Education, Learning Innovation and Accountability,, 2018)
This is the foundational book for the new series, Teacher Education, Learning Innovation and Accountability. The book canvasses research, practice and policy perspectives in teacher education across diverse geographic, social and political contexts. It explores the lifespan of teacher development from initial preparation through to graduate classroom practice as it occurs in an intensifying culture of standards and regulation. The characterization of initial teacher education (ITE) in a crucible of change permeates throughout the book. The chapters open up new ways of thinking about innovation and accountability in ITE and the professionalization of teaching, exploring fundamental questions, such as "Who are the actors in teacher preparation and how do they interact? How can we learn about the quality of teacher education? Where can we hear the voices of teacher educators and preservice teachers, as well as school-based teacher educators? What are the new and emerging roles of others in teacher education who have not been involved previously, including employing authorities?" (p. 22). While the book provides responses to these and other provocative questions, it also offers new insights into innovative teacher education from a wide range of policy and practice contexts.